Dynamic Analysis of Narrow Tilting Three Wheeled Vehicle (NTTWV) with LQG Control - Muhammad Fadlil Adhim; Unggul Wasiwitono (JMES The International Journal of Mechanical Engineering and Sciences, 2017)
The need for compact vehicles will increase in urban areas in the future. This paper propose solution by designing a vehicle that can combine advantage of car such as comfort and safety and the advantage of motorcycle such as efficiency and lightweight. The proposed vehicle has 3 wheels, 2 front wheels as steering wheels and the rear wheel as traction wheel. Active tilting system is used to give desired roll angel  that can resist the centrifugal force to maintain the vehicle stability. The goals of this research are to design dynamic model and control of NTTWV and its control system. The simulation result showed that the NTTWV rolls only 60% of ideal motorcycle rolling angle at same velocity and turning radius. The improvement of critical speed compared to non-tilting three-wheeled vehicle at steer angle = 5 deg and  10 deg are 193% and 171%.